An empirical analysis of public debt and government expenditure in South Africa - Thusini, Sphesihle; Mah, Gisele (Asian Development Policy Review, 2023)
The high rate of growth of public debt in African countries has stimulated debate among professionals, public representatives, and the general public on how government expenditure affects public debt levels. The primary focus of this paper is to study the relationship between public debt and government spending in South Africa. The methodology of this study employs the Johansen test of co-integration, the VECM, and the Granger causality test. The data period is from 1980 to 2020, and time series data was taken from the South African Reserve Bank and the International Monetary Fund. The findings of this study reveal a negative, statistically significant, and unidirectional causality coming from capital expenditure to public debt. Recurrent expenditure is positive and statistically significant, with unidirectional causality from public debt to recurrent expenditure. Inflation is positive and statistically significant; the causality result shows unidirectional causality, that is, from inflation to public debt. The study yielded positive outcomes and demonstrated statistical significance in relation to the relationship between the exchange rate and public debt. The practical implication is that the South African government should spend more borrowed money on capital expenditures. Secondly, public debt could be reduced by continuing with inflation targeting. Lastly, the government should be encouraged to borrow in local currency.